The Effect of Workload on Turnover Intention of Teachers at SMA Angkasa Adisutjipto Yogyakarta with Work Stress as a Mediation Variable and Psychological Empowerment as a Moderation Variable - Rahayu Rohmi Utami; Yuni Siswanti; C. Ambar Puji Harjanto (Westscience Press, 2024)
The objective of this study is to determine and analyse the effect of workload on turnover intention in teachers at SMA Angkasa Adisutjipto Yogyakarta, with work stress as a mediating variable and psychological empowerment as a moderating variable. The population of this study consisted of 38 teachers at SMA Angkasa Adisutjipto Yogyakarta. The sample of this study was selected from the population of teachers at SMA Angkasa Adisutjipto Yogyakarta. The analysis method employed in this study was partial least squares (PLS). The findings of this research analysis indicate that workload has a significant positive effect on turnover intention in teachers at SMA Angkasa Adisutjipto Yogyakarta. Furthermore, work stress mediates the effect of workload on turnover intention in teachers at SMA Angkasa Adisutjipto Yogyakarta. However, psychological empowerment does not moderate the effect of workload on turnover intention in teachers at SMA Angkasa Adisutjipto Yogyakarta.